1988
DOI: 10.1056/nejm198805123181906
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Yield of the Autopsy in a University Hospital and a Community Hospital

Abstract: To determine the extent to which autopsies yield unexpected findings that are relevant to the patient's death and whether cases with a high yield of such findings can be identified selectively, we studied a total of 233 autopsies at a university hospital and at a community hospital. The rates at which autopsies detected major unexpected findings whose premortem diagnosis would probably have improved survival were 11 percent at the university hospital and 12 percent at the community hospital. Major unexpected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
2
18

Year Published

1989
1989
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(106 citation statements)
references
References 26 publications
3
83
2
18
Order By: Relevance
“…2 -A necrópsia tem sido freqüentemente considerada como um dos métodos mais serepresentado pela média da estimativa da confirmação anatomopatológica do diagnóstico clí-nico: 70,97% (286-83/335 = ) significando que mesmo quando o diagnóstico clínico possa estar correto há um substancial número de outros diagnósticos de importância que serão revelados somente na necróp-sia 8,11,19,23,28,32,38,39 .…”
Section: Resultsunclassified
See 1 more Smart Citation
“…2 -A necrópsia tem sido freqüentemente considerada como um dos métodos mais serepresentado pela média da estimativa da confirmação anatomopatológica do diagnóstico clí-nico: 70,97% (286-83/335 = ) significando que mesmo quando o diagnóstico clínico possa estar correto há um substancial número de outros diagnósticos de importância que serão revelados somente na necróp-sia 8,11,19,23,28,32,38,39 .…”
Section: Resultsunclassified
“…Tem-se demonstrado, no entanto, que mesmo quando essa certeza possa existir, a necrópsia leva a alterações significativas nos diagnósticos anteriormente formulados 8,10,23,28 .…”
Section: Introductionunclassified
“…In 1983, these discrepancies were classified by Goldman et al (9) considering their importance for clinical practice. He suggested that attention be given to therapeutically significant errors whose correction could contribute to medical care improvement (4,8,10,11). These errors correspond to Goldman's classes I and II: significant diagnosis, for which the detection during lifetime would probably change the management and result in cure or prolonged survival, and significant diagnosis, for which detection during a lifetime would probably not change the management because there was no better therapy at that time (9).…”
Section: Introductionmentioning
confidence: 99%
“…Hastaların %10'unda Lupus antikoagülanı bulunmuş-tur (12). Hastaların %20'si antikardiolipin antikorları ve lupus antikoagülanı, ya da her ikisini taşır (13). KTEPH hastalarının %39'unda Faktör VIII plazma düzeyi yüksek bulunmuştur (14).…”
Section: Yatkınlık Oluşturan Unsurlarunclassified